The octamer-binding proteins form multi-protein--DNA complexes with the HSV alpha TIF regulatory protein. - Kristie, T M (1989)
The herpes simplex virus transactivator, alpha TIF, stimulates transcription of the alpha/immediate early genes via a cis-acting site containing an octamer element and a conserved flanking sequence. The alpha TIF protein, produced in a baculovirus expression system, nucleates the formation of at least two DNA--protein complexes on this regulatory element. Both of these complexes contain the ubiquitous Oct-1 protein, whose POU domain alone is sufficient to allow assembly of the alpha TIF-dependent complexes. A second member of the POU domain family, the lymphoid specific Oct-2 protein, can also be assembled into similar complexes at high concentrations of alpha TIF protein. These complexes contain at least two cellular proteins in addition to Oct-1. One of these proteins is present in both insect and HeLa cells and probably recognizes sequences in the cis element. The second cellular protein, only present in HeLa cells, probably binds by protein-protein interactions.